The Pandemic Made Librarians Step Out of Frames (Journal of EAHIL, 2022)
The library of Tallinn Health Care College is a professional library, which collects, maintains, and makes the health care literature and databases available for users. Major changes in the world have brought new services to the library of Tallinn Health Care College, as well as to all other libraries. The situation has made librarians think about the ways to further support teaching and research in the College. In addition, the requirements of the College present challenges for librarians resulting in us to step out of the frames and test ourselves in a new role.